Characteristic of Manyar Bird Nest (Ploceus manyar) in Kuta Baro Subdistrict Aceh Besar Regency - Dila Maiyana; Abdullah Abdullah; Devi Syafrianti; Safrida Safrida; Khairil Khairil (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2021)
Manyar Bird (Ploceus manyar) is a member of Ordo Passeriformes that can be found around rice fields because the feed is grain. Research with the title